Colonic 15-PGDH levels are stable across distance and time, and are not perturbed by aspirin intervention - Fink, Stephen P. (2013)
BACKGROUND & AIMS: 15-hydroxprostaglandin dehydrogenase (15-PGDH) mediates a colon neoplasia suppressor pathway, acting through metabolic antagonism of cyclooxygenase (COX)-mediated colon carcinogenesis. To determine whether the colon tumor prevention activity of 15-PGDH acts as a constant or variable effect among individuals, we determined whether 15-PGDH levels remains stable over subsite and time in the human colon, determined the extent of differences in 15-PGDH levels between different individuals, and determined whether or not 15-PGDH modulation mediates any part of the anti-colon tumor effect of aspirin. METHODS: Using real-time PCR, we measured 15-PGDH mRNA, determining the correlation of 15-PGDH level in replicate colon biopsies, in biopsies from throughout the length of the colon, in repeat biopsies taken 4 months apart, and in paired biopsies of individuals taken before and after aspirin treatment, and by western for 15-PGDH protein in mice. RESULTS: Colonic 15-PGDH levels varied 4.4-fold across the human population. Within individuals, 15-PGDH levels proved highly reproducible (r=0.81 in duplicate biopsies) and stable along the length of the colon, with average 15-PGDH levels deviating by only 17% from rectum to cecum. An individual’s 15-PGDH levels are also highly stable over time, with a median coefficient of variation over a 4-month interval of only 12%. Last, colonic 15-PGDH levels proved resistant to alteration by aspirin, with only a 10% difference in 15-PGDH levels measured before and after aspirin treatment. CONCLUSIONS: 15-PGDH levels vary across the population in a stable and reproducible manner, and are resistant to alteration by aspirin. 15-PGDH represents an independent target for modulation by candidate colon tumor chemopreventive agents.